Antiulcerogenic action of ethanolic extract of the resin from Virola surinamensis Warb. (Myristicaceae) - Hiruma-Lima, Clélia Akiko [UNESP]; Batista, Leonia Maria; Albino de Almeida, Ana Beatriz; Magri, Luciana de Pietro; Santos, Lourdes Campaner dos [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina (Elsevier B.V., 2009)
Ethnopharmacological relevance: Virola surinamensis (Myristicaceae), popularly known as mucuiba, ucuuba or ucuuba do igapo is a large tree that grows abundantly in Varzea forest and on river banks in the Brazilian states of Amazonas and Tocantins. The resin obtained by cuts on the stem bark is a reputed folk remedy in its natural form for the treatment of ulcer, gastritis inflammation and cancer.Aim of the study: The present work evaluated the pharmacological activity of the resin obtained from bark of V surinamensis as antiulcerogenic in experimental in vivo model in order to observe whether its traditional use is justified.Materials and methods: The preventive action of ethanolic extract of V surinamensis was evaluated in experimental in vivo models in rodents that simulated this disease in human gastric mucosa.Results: Oral administration of acidified ethanol solution produced severe hemorrhagic lesions in glandular mucosa with ulcerative lesion of 50 +/- 11.5 mm. In animals pretreated with V surinamensis (500 mg/kg, p.o.) a significant inhibition of mucosal injury of 2.40 +/- 0.56 mm (95% inhibition) was detected. The V. surinamensis, at the same dose, also reduced significantly (p < 0.05) the formation of gastric lesions induced by indomethacin (39%), stress (45%) and by pylorus ligature in mice (31%) when compared to animals treated with vehicle. The extract from V surinamensis exerts gastroprotective action only when this extract contacts gastric mucosa (oral route) with. increased pH values and reduced H(+) concentration of gastric contents. The ethanolic extract of V surinamensis resin was analyzed by TLC and spectrometric methods (NMR and ES-MS) and the main constituent of this extract was epicatechin.Conclusions: We suggest that the epicatechin present in V surinamensis resin may be among active principles responsible for the antiulcer activity shown by the tested resin but their used suggest carefulness because toxicological symptoms mentioned by population. (C) Published by Elsevier B.V.
Keywords: Virola surinamensis; Myristicaceae; Gastric ulcer; Epicatechin; Flavonoids